(untitled) (Eurasian Research Bulletin, 2022)
Since the birth of human, he begins receiving a plethora of information from external environment and events. Not only human’s physical activeness but also his mental knowledge starts to enhance. However, if you begin to understand what development of human is, you could know the availability of extraordinary and challenging process